2003
DOI: 10.1259/bjr/18937619
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary lesions associated with Sjögren's syndrome: radiographic and CT findings

Abstract: The aim of this study was to analyse and compare the chest radiographic and CT findings in patients with primary and secondary Sjögren's syndrome. We retrospectively evaluated the frequency of abnormality and findings of both the chest radiography (n=107) and CT (n=59) in patients with Sjögren's syndrome. Abnormal cases were classified into five patterns based on predominant CT findings. Chest radiographic and CT abnormalities were seen in 24 (22%) and in 34 (58%) patients, respectively. Most frequently observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 14 publications
1
55
0
Order By: Relevance
“…This combination of signs is in accordance with LIP. In the study by MATSUYAMA et al [110] in patients with both pSS and secondary SS, it has been observed that centrilobular abnormalities and lymphoproliferative disorders pattern were characteristic in patients with pSS.…”
Section: Radiological Featuresmentioning
confidence: 92%
See 1 more Smart Citation
“…This combination of signs is in accordance with LIP. In the study by MATSUYAMA et al [110] in patients with both pSS and secondary SS, it has been observed that centrilobular abnormalities and lymphoproliferative disorders pattern were characteristic in patients with pSS.…”
Section: Radiological Featuresmentioning
confidence: 92%
“…In patients with pSS, it has been found that bilateral lung infiltrates is the most common pattern seen on chest radiography [109]. It also has been found that in patients with both pSS and secondary SS, 22% had chest radiography abnormalities, with linear and reticular opacities being the most frequent finding [110].…”
Section: Radiological Featuresmentioning
confidence: 99%
“…When investigated systematically, prevalence increases to between 43% and 75% [37]. Computed tomography (CT) scan abnormalities are found in 34-50% of patients [38]. The annual incidence of respiratory manifestations is estimated at 10% (±3%) 1 year after diagnosis of Sjögren's syndrome and increases to 20% (±4%) by 5 years [6].…”
Section: Sjögren's Syndrome Patients With Pulmonary Involvementmentioning
confidence: 99%
“…Chest radiographs can show bilateral lung infiltrates with linear and reticular opacities (10-30%) [36,38,46]. Radiological abnormalities are not correlated with PFT and respiratory symptoms [91].…”
Section: Ild In Sjögren's Syndromementioning
confidence: 99%
“…2,4,21 Prevalence of lung involvement is SS varies widely (9%-75%) according to the diagnostic modalities and studied population. 36 The most frequent pulmonary manifestations of SS are ILD and airways disease. 2 The most common ILD pattern identified in patients with SS is NSIP, with other frequent patterns being OP, UIP, and LIP.…”
Section: Sjögren Syndromementioning
confidence: 99%